Socio-Economic Life of Steenkolen Maatschappij Parapattan Workers at Silo Port (1912-1957) - Salsabila, Nurul Septia; Kusumawijaya, Rizal Izmi; Asnar, Asnar (Yupa: Historical Studies Journal, 2024)
This research aims to explain how the socio-economic life of Steenkolen Maatschappij Parapattan workers at Silo Port from 1912 to 1957. The type of research used is historical research which includes Heuristics, Criticism, Interpretation, and Historiography. The focus of the research discusses the general description of Steenkolen Maatschappij Parapattan, the labor employment system, the condition of job availability, and labor conflicts. The results show that initially, the laborers who worked at Steenkolen Maatschappij Parapattan were local laborers from the Berau region, but in 1919 many laborers were brought in from outside the region, especially from Java to fill the shortage of human resources. In addition, Steenkolen Maatschappij Parapattan was not only engaged in mining but also plantations and timber extraction. Steenkolen Maatschappij Parapattan also built infrastructure to support the company's activities. In 1926, there was a labor conflict that occurred due to exploitation and the presence of mass organizations in the Berau region. The employment opportunities available in the Berau region from 1912 to 1957 were dominated by mining. However, there were also jobs in plantations, timber extraction, education, and sea transportation. The rapid development of the Berau region created many jobs.